Pinevale Highschool Yearbook, 1964 - Lowndes County Historical Society (Valdosta State University Archives and Special Collections, 1964)
Pinevale Highschool Yearbooks, "The Tiger," 1964. Valdosta, Georgia. Original copies of the yearbooks are from Lowndes County Historical Society and were digitized by Mark George, Summer 2023.
1 electronic record(s). PDF document and 82 image scans.
Keywords: School yearbooks; African American high school students; High schools; Valdosta (Ga.)